News in Digital Media Era - Rodyoo, Chanida (Parichart Journal, 2020)
News is the main content of mass media, meaning of the occurred events are factsand have elements of events which can be considered as having valuableness, importance and impact that people should be informed. However, with rapidly changing technology, internet media has become greater role to the society. People or recipients prefer consuming news on this type of media as well, and the qualifications of internet or new media is digitalization, able to send information and data in various dimensions (many to many), becoming the combination of interpersonal and mass media communications. Therefore, there are more advantages over traditional mass media in interactivity between messenger and receiver. Plus, digital media has created changes for mass communication paradigm in all aspects, including the work process to produce news content. This changed the definition of the word “news” which has been currently using. Considering elements of the event, which will be presenting as news, is different from traditional journalism scheme. The main elements in presenting news reports is more diverse and complex, and style of presenting news is more modern and interesting. Presenting news in digital media era should use appropriate techniques and principle for media nature, as well as recipients’ nature which changing according to technologies.